Modeling Biological Systems Using Functional State Spaces - Williams, Andy (My University, 2022)
The technique of Human-Centric Functional Modeling represents systems as having a set of functions through which the system might transition from one state to another. These are functional states in that each state is described in terms of the functions available to transition to adjacent states. All possible behaviors of the system are then described by a graph containing a network of nodes representing such functional states, where those nodes are connected by edges representing the processes through which those functional states transition between each other. This paper outlines a hypothesis regarding how biological systems might come to occupy such a graph, also called a functional state space, and outlines some questions that must be answered in order to validate this hypothesis.
Keywords: biology; functional state space; human-centric functional modeling